Understanding Statistics Using R - Schumacker, Randall; Tomek, Sara (Springer, 2013)
This book was written as a supplemental text for use with introductory or intermediate statistics books. The content of each chapter is appropriate for any undergraduate or graduate level statistics course. The chapters are ordered along the lines of many popular statistics books so it should be easy to supplement the chapter content and exercises with your statistics book and lecture materials. The content of each chapter was written to enrich a students’ understanding of statistics using R simulation programs. The chapter exercises reinforce an understanding of the statistical concepts presented in the chapters. Computational skills are kept to a minimum in the book by including R script programs that can be run for the exercises in the chapters. Students are not required to master the writing of R script programs, but explanations of how the programs work and program output are included in each chapter. R is a statistical package with an extensive library of functions that offers fl exibility in writing customized statistical routines. The R script commands are run in the R Studio software which is a graphical user interface for Windows. The R Studio software makes accessing R programs, viewing output from the exercises, and graph displays easier for the student.